2016
DOI: 10.1111/ibi.12342
|View full text |Cite
|
Sign up to set email alerts
|

Feather‐degrading bacteria, uropygial gland size and feather quality in House SparrowsPasser domesticus

Abstract: 2Feathers are dead integumentary structures that are prone to damage and thus show gradual degradation over the course of a year. This loss of quality might have negative fitness consequences. Feather-degrading bacteria are some of the most prevalent featherdegrading organisms, yet the relationship between feather-degrading bacteria load and flight feather quality has rarely been assessed. We studied this relationship in free-living House Sparrows during breeding and non-breeding annual lifecycle stages. We al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
21
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 48 publications
0
21
0
1
Order By: Relevance
“…Indeed, experimental modifications of the nest microbiota have been shown to lead to changes of feather microbiota (Jacob, Immer, et al., ), and had significant consequences for host phenotype and fitness (Jacob et al., ). Coating feathers with secretions from the uropygial gland might allow a bird to control colonization of body feathers by environmental microorganisms to some degree (Czirjak et al., ; Fülöp et al., ; Jacob, Immer, et al., ; Møller et al., ; Ruiz‐Rodriguez, Valdivia, et al., ; Shawkey et al., ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, experimental modifications of the nest microbiota have been shown to lead to changes of feather microbiota (Jacob, Immer, et al., ), and had significant consequences for host phenotype and fitness (Jacob et al., ). Coating feathers with secretions from the uropygial gland might allow a bird to control colonization of body feathers by environmental microorganisms to some degree (Czirjak et al., ; Fülöp et al., ; Jacob, Immer, et al., ; Møller et al., ; Ruiz‐Rodriguez, Valdivia, et al., ; Shawkey et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Almost all bird species possess an external gland, the uropygial gland, which produces oily secretions used to coat feathers. Well known for their waterproofing properties (Jacob & Ziswiler, 1982) and their role in plumage signalling and communication (Lopez-Rull, Pagan, & Macias Garcia, 2010;Piault et al, 2008;Piersma, Dekker, & Sinninghe Damst e, 1999), these secretions have also been suggested to function as an antimicrobial defence mechanism used to regulate bacterial communities on feathers (Czirjak et al, 2013;F€ ul€ op, Czirj ak, Pap, & V ag asi, 2016;Jacob, Immer, et al, 2014;Leclaire, Pierret, Chatelain, & Gasparini, 2014;Mart ın-Vivaldi et al, 2009;Møller, Czirjak, & Heeb, 2009;Shawkey, Pillai, & Hill, 2003). Accordingly, by experimentally manipulating great tit (Parus major) microbiota, Jacob, Immer, et al (2014) demonstrated that individuals modify the quantity and chemical composition of uropygial secretions produced depending on their exposure to bacteria.…”
mentioning
confidence: 99%
“…Because feather damage could decrease flight performance, body insulation and fitness (Proctor and Lynch , Barbosa et al ), birds with compromised feather condition should have lower survival prospects (Booth et al , Clayton et al , but also see Merilä and Hemborg ). Uropygial glands may play an essential role in the regulation of feather‐degrading bacteria, thus minimizing the impact of these pathogens on feather quality (Fülöp et al , but also see Czirják et al 2013 and Giraudeau et al for opposite results). Consequently, birds with larger uropygial glands should have better plumage condition and therefore enjoy higher survival prospects.…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, birds chronically infected with malaria develop more severe clinical disease when co‐infected with Mycoplasma (Dhondt et al ). Because larger uropygial glands may prevent bacterial infection (Fülöp et al ), infected house martins secreting higher volumes of uropygial oil may prevent deadly co‐infections with malaria and bacteria. However, we should be cautious in our conclusions because our results rely on comparisons with low sample size of malaria infected house martins that survived to the next breeding season (n = 5) (Lemoine et al ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation